Effects of body weight support training on balance and walking function in stroke patients: a systematic review and meta-analysis - Jiang, Zhaoxiang; Zhang, Xinxin; Fu, Qian; Tao, Yimin (Frontiers in Neurology, 2024)
Objective To comprehensively and quantitatively evaluate the impact of body weight support training (BWST) on balance and gait function in stroke patients based on an evidence-based basis and to identify the most effective intervention strategies. Methods PubMed, Web of Science, The Cochrane Library, CNKI, Wanfang, and Chinese SinoMed Database were searched until November 25, 2023. Quality assessment and meta-analysis were performed using RevMan 5.2 and Stata 14.0 software. Results A total of 31 randomized controlled trials involving 1,918 patients were included in the study. The meta-analysis demonstrated that body weight support training (BWST) significantly improved Berg Balance Scale (BBS) scores (MD = 3.60; 95% CI: 1.23 to 5.98; p = 0.003), gait speed (SMD = 0.77; 95% CI: 0.38 to 1.15; p < 0.0001), and step length (SMD = 0.46; 95% CI: 0.19 to 0.72; p = 0.0008) in stroke patients compared to conventional rehabilitation. For enhancing balance function, the most effective interventions were identified as a disease duration of 3–6 months (MD = 5.16; 95% CI: 0.76 to 9.57; p = 0.02), intervention time of 4–8 weeks (MD = 5.70; 95% CI: 2.90 to 8.50; p < 0.0001), a maximum body weight support level above 30% (MD = 3.80; 95% CI: 1.48 to 6.13; p = 0.001), and a maximum training walking speed of 0.2 m/s or more (MD = 4.66; 95% CI: 0.37 to 9.70; p = 0.03). For improving walking function, the optimal interventions were also a disease duration of 3–6 months (gait speed: SMD = 0.59; 95% CI: 0.15 to 1.03; p = 0.008; step length: SMD = 0.27; 95% CI: 0.06 to 0.56; p = 0.04), intervention time of 4–8 weeks (gait speed: SMD = 1.01; 95% CI: 0.44 to 1.59; p = 0.0006; step length: SMD = 0.83; 95% CI: 0.54 to 1.12; p < 0.00001), a maximum body weight support level above 30% (gait speed: SMD = 0.79; 95% CI: 0.36 to 1.22; p = 0.0003; step length: SMD = 0.79; 95% CI: 0.47 to 1.11; p < 0.00001), and a maximum training walking speed of 0.2 m/s or more (gait speed: SMD = 1.26; 95% CI: 0.62 to 1.90; p = 0.0001; step length: SMD = 0.85; 95% CI: 0.38 to 1.31; p = 0.0003). Conclusion Compared with conventional rehabilitation training, BWST demonstrates superior efficacy in enhancing balance and walking function in stroke patients, with a consistent optimal intervention strategy. The most effective program includes a disease duration of 3–6 months, an intervention period of 4–8 weeks, a maximum body weight support of 30% or more, and a maximum training walking speed of 0.2 m/s or greater. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022358963.